The stock market course - Fontanills, George; Gentile, Tom (New York : Wiley, 2001)
A complete guide, step-by-step guide, the book covers all the bases, from mastering market terminology to performing technical analysis.
Includes bibliographical references and index.
osc 12/07/2016
Loans
Keywords: Stocks; Trading - stocks; Broad market; United states